Pain that does not interfere with daily life—a new focus for population epidemiology and public health?. Issue 2 (February 2019) - Jordan, Kelvin P.; Sim, Julius; Croft, Peter; Blyth, Fiona
Abstract : Supplemental Digital Content is Available in the Text.